The Analysis of Salinity Concentrations on The Coast of Pasuruan by Utilizing Visible Wavelength Aqua MODIS Image Data - Hendrata Wibisana; Siti Zainab; Farida Hardaningrum (Nusantara Science and Technology Proceedings, 2024)
Changes in salt levels in the aquatic environment play an important role in the life of coastal ecosystems. These changes can be known by looking at the development of living things around the main waters on the coast, where the place is widely used for fishermen to look for fish. This study aims to determine the distribution of salinity in the coastal environment so that the existing patterns of dissolved salt in these waters can be known. The method used this time is to utilize the algorithm of the visible light channel owned by the Aqua MODIS satellite image, namely wavelengths of 412 nm, 531 nm and 667 nm. The results obtained from the algorithm are that the blue canal from the satellite image provides a more optimal result compared to the ratio of the other 2 channels, where from the calculation results a significant correlation is obtained around 0.539 or about 53.9% of the satellite image data with the ratio of the blue and red canals has a correlation with the salinity distribution value on the coast of Pasuruan. The algorithm of the mathematical model that emerged was the logarithmic model Sal= 15.664*ln(Rrs_412)+115.82. In the future, the wavelength ratio can be used to study the effect of salinity concentration temporally by using different sensors in order to obtain maximum results.